2021
DOI: 10.3390/pharmaceutics13060860
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Posterior Capsule Opacification in the Development of Intraocular Lens Materials

Abstract: Posterior capsule opacification (PCO) is the most common complication arising from the corrective surgery used to treat cataract patients. PCO arises when lens epithelial cells (LEC) residing in the capsular bag post-surgery undergo hyper-proliferation and transdifferentiation into myofibroblasts, migrating from the posterior capsule over the visual axis of the newly implanted intraocular lens (IOL). The developmental pathways underlying PCO are yet to be fully understood and the current literature is contradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 119 publications
(275 reference statements)
0
19
0
Order By: Relevance
“…5,6 PCO is the main factor that affects vision recovery and causes blindness. 7 The incidence of PCO is about 20-40% in adults and almost 100% in children. 8,9 Nd:YAG laser capsulotomy is the only effective clinical treatment at present.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 PCO is the main factor that affects vision recovery and causes blindness. 7 The incidence of PCO is about 20-40% in adults and almost 100% in children. 8,9 Nd:YAG laser capsulotomy is the only effective clinical treatment at present.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [4], [10] found that most patients were in the age range of 41 years to 80 years, and Ayuningtyas et al [8] showed a median age of 65 years with a range of 42 years to 87 years. In various studies [11], [12], [13], [14], [15], [16] , the period between patients who underwent cataract surgery and PCO formation has been reported to occur from five months to three years. In this study, PCO diagnosis was established after a median of 12 months, ranging from 8.2 months to 26.3 months after cataract extraction.…”
Section: Resultsmentioning
confidence: 99%
“…However, their visual axis was found to be clear six months after surgery, with the average age at surgery of 29.1 months. 23,24 Thus far, there is no data regarding rubella as the cause of infection that can initiate PCO occurrence.…”
Section: Discussionmentioning
confidence: 99%